PENGEMBANGAN PIRANTI LUNAK SISTEM PROSES BERSIFAT USER FRIENDLY DENGAN SCILAB (Open Source Software) - Sasongko, Setia Budi (METANA, 2007)
Abstract Requirement of software is necessary for the process system-computer simulation. ln reality, costly of software is one of restriction for the software development. However, the costly constraint can be solved using open source software such as Scilab and OpenOffice. The goa lof this article formulates user friendly program of the process system. Scilab program by Graphical User Interface (GUI) and interaction with Open Office-Cale for the data-base physical property. Scilab program has been listed in this article and algorithme of rhe program as the methodology has been presented in this article. Results of the simulation program indicate goodfinding for the process system. Â  Kata kunci : scilab; open office, simulasi komputer; oss (open source sortuare), Antar Muka Pcngguna - Graphical User Interface (GUI).